Evaluating successes and challenges for effective governance of privately protected areas in Australia - Brugler, Sarah (Frontiers in Conservation Science, 2023)
Australia has one of the world's largest privately protected area (PPA) estates and has been seen as a world leader in establishing PPAs, with significant growth since 2000. Despite the policy expectation that PPAs will continue to grow in Australia, there has been limited policy or academic consideration of the legal and governance arrangements that are best placed to enable this. This article uses adaptive governance as a conceptual framework to analyze the governance of conservation covenant regimes in Australia, with a particular focus on the State of Victoria, and considers the opportunities and challenges for conservation covenant regimes to adapt and evolve to meet emerging environmental policy initiatives. The analyses and findings, while focused on the Australian context, are expected to have applicability to other jurisdictions that are focused on implementing the Kunming-Montreal Global Biodiversity Framework and policies related to protected areas, private land conservation, ecosystem restoration, and climate adaptation.